Characterisation of low-level pyrasulfotole resistance and the role of herbicide translocation in wild radish (Raphanus raphanistrum) - Danica E. Goggin; Candy M. Taylor; Roberto Busi; Ken Flower (Pesticide Biochemistry and Physiology, 2024)

Microbial glucoamylases: structural and functional properties and biotechnological uses - Natael M. Wayllace; Mariana Martín; María V. Busi; Diego F. Gomez-Casati (World Journal of Microbiology and Biotechnology, 2023)

Identification, molecular and biochemical characterization of a novel thermoactive and thermostable glucoamylase from Thermoanaerobacter ethanolicus - Natael M. Wayllace; Nicolas Hedín; María V. Busi; Diego F. Gomez-Casati (Biotechnology Letters, 2022)

Isolation and characterization of plant growth promoting rhizobacteria and their biocontrol efficacy against phytopathogens of tomato ( Solanum lycopersicum L.) - Paramanantham Parasuraman; Subha Swaraj Pattnaik; Siddhardha Busi; Najat Marraiki; Abdallah M. Elgorban; Asad Syed (Plant Biosystems, 2022)

A morphological, reproductive, and molt phenology database for 379 bird species from the Colombian Tropical Andes - Leydy J. Cardona‐Salazar; Yeny A. Benavides‐Ossa; Ángela M. Vargas‐Daza; Juan F. Betancurt‐Grisales; Mauricio Bohada‐Murillo; Estefani T. Martínez‐Sánchez; Marelid Cardona‐Romero; Ana Busi; William D. Tobón‐Escobar; Mateo Ortíz‐Giraldo; Daniela Gómez Castillo; Johnathan Alvarez‐Londoño; et al. (Ecology, 2020)
The Colombian Tropical Andes are one of the regions with highest bird diversity on Earth. However, information on bird morphology, reproductive phenology, and molt is particularly scarce in this region. Also, this region is heavily impacted by deforestation, and it is vulnerable to climate change. Hence, providing baseline information on life history and morphological traits will be essential to support future research on functional diversity, climate change effects, conservation, evolution, and phenology. To fill this gap, we have compiled information on bird distribution, morphology, molt, and reproductive phenology at 52 localities of the Department of Caldas, covering an elevation range between 148 and 3845 m. This compilation comprises a wide range of habitats, including native forests, forestry plantations, croplands, and paramo. Our database presents information for 3,398 records belonging to 379 bird species (representing 23 orders, 53 families, and 258 genera). From those records, 2,843 correspond to information collected in the field between 2008 and 2019, and the remaining 555 records correspond to specimens deposited in the Natural History Museum of the Caldas University, collected between 1969 and 2014. We measured nine morphological traits from all specimens: total culmen, gape, bill width, bill depth, tarsus, wing length, tail length, total length, and mass. We also have reproductive condition information for 257 species and molt information available for 378 species. The information contained in this data set represents ~20% of the Colombian avifauna and ~11% of the bird species richness in South America. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Altered levels of mitochondrial NFS1 affect cellular Fe and S contents in plants - Alejandro M. Armas; Manuel Balparda; Valeria R. Turowski; Maria V. Busi; Maria A. Pagani; Diego F. Gomez-Casati (Plant Cell Reports, 2019)

Antimicrobial photodynamic activity of toluidine blue encapsulated in mesoporous silica nanoparticles against Pseudomonas aeruginosa and Staphylococcus aureus - Paramanantham Parasuraman; Asha P. Antony; Sruthil Lal S. B; Alok Sharan; Busi Siddhardha; Kaviyarasu Kasinathan; Needa A. Bahkali; Turki M. S. Dawoud; Asad Syed (Biofouling, 2019)

No fitness cost of glyphosate resistance endowed by massive EPSPS gene amplification in Amaranthus palmeri - Martin M. Vila-Aiub; Sou S. Goh; Todd A. Gaines; Heping Han; Roberto Busi; Qin Yu; Stephen B. Powles (Planta, 2014)

Biotransformation of α-Pinene to Terpineol by Resting Cell Suspension of Absidia corulea - Busi Siddhardha; M. Vijay Kumar; U. S. N. Murty; G. S. Ramanjaneyulu; S. Prabhakar (Indian Journal of Microbiology, 2012)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

MADS-box genes expressed during tomato seed and fruit development - María Victoria Busi; Claudia Bustamante; Cecilia D'Angelo; Mauricio Hidalgo-Cuevas; Silvana B. Boggio; Estela M. Valle; Eduardo Zabaleta (Plant Molecular Biology, 2003)